Kinesio taping in conservative treatment of mild-to-moderate cases of carpal tunnel syndrome = Kinesio taping w leczeniu zachowawczym łagodnego i umiarkowanego przebiegu zespołu cieśni nadgarstka - Kocjan, Janusz (Journal of Education, Health and Sport, 2016)
Kocjan Janusz. Kinesio taping in conservative treatment of mild-to-moderate cases of carpal tunnel syndrome = Kinesio taping w leczeniu zachowawczym łagodnego i umiarkowanego przebiegu zespołu cieśni nadgarstka. Journal of Education, Health and Sport. 2016;6(9):604-609. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.155060 http://ojs.ukw.edu.pl/index.php/johs/article/view/3886 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016. KINESIO TAPING IN CONSERVATIVE TREATMENT OF MILD-TO-MODERATE CASES OF CARPAL TUNNEL SYNDROME KINESIO TAPING W LECZENIU ZACHOWAWCZYM ŁAGODNEGO I UMIARKOWANEGO PRZEBIEGU ZESPOŁU CIEŚNI NADGARSTKA JANUSZ KOCJAN Medical University of Silesia, Doctoral Studium of School of Medicine, Katowice, Poland Śląski Uniwersytet Medyczny, Studium Doktoranckie Wydziału Lekarskiego w Katowicach SUMMARY Carpal tunnel syndrome (CTS) is the most common peripheral neuropathy. Severe cases are usually treated surgically, while conservative treatment is recommended in mild to moderate cases. The aim of the study was to investigate the effect of kinesiotaping (KT) on pain level, hand functional status, and carpal joint range of movement compared with that of „wait and see” group in mild-to-moderate cases of CTS. In this randomized study, 32 participants (38 hands) of ages between 35-50 years with clinical and electrodiagnostic evidence of carpal tunnel syndrome were allocated into one of two groups: (1) experimental Kinesiotaping group (KG, tape applied with 40% tension from hand to medial epicondyle), and (2) Control Group („wait and see” - without tape applied). Following measures were used in the present study: BCTQ, DASH and VAS scale. In any of the groups reported no statistically significant improvement in the analyzed variables. In conclusion, there is no evidence on the efficacy of KT application for the treatment of CTS.